2015
DOI: 10.1080/10640266.2015.1090869
|View full text |Cite
|
Sign up to set email alerts
|

Recovered eating disorder therapists using their experiential knowledge in therapy: A qualitative examination of the therapists’ and the patients’ view

Abstract: In the eating disorder (ED) field there is a lack of guidelines regarding the utilization of recovered therapists and the experiential knowledge they can bring to therapy. In this study, a qualitative design was used to examine recovered eating disorder therapists using their experiential knowledge and how this influences therapy and the patients they treat. Respectively, 205 patients (response rate 57%), and 26 recovered therapists (response rate 75%) completed a questionnaire about advantages and disadvantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…In EDs, recovered therapists can be quite empathetic, but utilizing one’s own experience effectively in the treatment of others is a complex psychotherapeutic tool that requires maturity and insight about one’s own biases, with recovery of the provider thought to be important for success as a care provider. 3335 Unfortunately, 12% of the dietitians that did not report ever obtaining treatment of an ED (combined D-HC and D-ON groups) scored above the screening threshold suggestive of a current ED. 26,27 ED professionals that have not fully recovered may have a high risk for relapse for themselves, and may not even be aware of their own cognitive biases.…”
Section: Discussionmentioning
confidence: 99%
“…In EDs, recovered therapists can be quite empathetic, but utilizing one’s own experience effectively in the treatment of others is a complex psychotherapeutic tool that requires maturity and insight about one’s own biases, with recovery of the provider thought to be important for success as a care provider. 3335 Unfortunately, 12% of the dietitians that did not report ever obtaining treatment of an ED (combined D-HC and D-ON groups) scored above the screening threshold suggestive of a current ED. 26,27 ED professionals that have not fully recovered may have a high risk for relapse for themselves, and may not even be aware of their own cognitive biases.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential benefits of FBIs is that it allows patients to gain experiential knowledge of what it is like to have a different body with different physical dimensions. Experiential knowledge has the ability to enhance clinical insight from the perspectives of both the clinicians and the patients (De Vos et al, 2016). Moreover, the ability to acquire experiential knowledge within clinical settings may expand the potential of patients with a rigid thinking pattern who would otherwise drop out because of a lack of emotional engagement (Riva, 2003).…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Early research in this area suggests, in line with the findings from the current study, that peer-mentoring can increase hope for current sufferers [ 57 , 58 ]. A recent study has examined the effect of therapists working in the field of eating disorders with lived experience of an eating disorder themselves and found that using experiential knowledge can have advantages such as providing insights into the recovery process and enhancing hope for recovery but that this knowledge must be shared thoughtfully and without specific details about symptomatology [ 59 ]. The current study adds to the emerging research in the field of eating disorders regarding recovery-oriented approaches and lived-experience integration however, much more research is needed.…”
Section: Discussionmentioning
confidence: 99%